(untitled) (Journal of Parents and Teachers, 2014)
Educational centers must offer programs and services for guidance and prevention of drug dependencies in the school environment, these will be aimed at their students and their parents. Teachers and schools are the main resource to develop an education that guides and informs children and, especially, adolescents about this topic. However, families and institutions must also make an effort to educate the new generations on this subject.